Life expectancy: complex measures of the length and the health related quality of life (Italian Journal of Public Health, 2008)
Background: Life expectancy is one of the most frequently used indicators to assess mortality and the healthof a population. It is a synthetic measure of mortality, which has the advantage of allowing for comparisonsover time and between different groups, while eliminating the influence of the age structure of the population.Life expectancy has the advantage of being very easy to understand, although it needs to be interpretedwithin the context of the complex system of hypothesis that generates it. This is even more important forhealth expectancies and health gap measures, which are synthetic indicators that take into account bothsurvival and health condition of a population.Methods: It is given a description of the most frequently used methods to calculate life expectancy, healthexpectancies and health gap measures. Measures of health expectancy are disability free life expectancy andhealthy life expectancy. As health gap measures, frequently are used DALYs (Disability Adjusted Life Years).Discussion: There are various bodies and central government agencies that either have management data orcarry out statistical systematic surveys and disability surveys. Statistically speaking, the worst aspect of thisscenario is that it creates confusion and uncertainty among the end users of this data, namely the policy makers.At an international level the statistical data on disability is scarcely comparable among countries, despite hugeefforts on the part of international organisations to harmonize classifications and definitions of disability.Results and Conclusions: There are several methods to compute life expectancy, each of these has someadvantages and some disadvantages. Usually life expectancy is used also to account for the health status ofpopulation. Actually with the growing role of chronic and degenerative diseases, the increased number ofyears lived are potentially independent from increase in health status of the population. Quantity and qualityof live are not anymore strictly related, then a higher quantity of life does not equate to a better quality of life.For this reason are used health expectancies measures that are very useful morbidity-mortality indicatorsable to summarize information on quantity and quality of the years lived
Keywords: life expectancy; health expectancies; health gap measure; methodology